An ethical and legal analysis of different models of autonomy in healthcare decision making based on family dynamics in Malaysia / Wellester Alvis - Alvis, Wellester (2023)
In the current era of self-determination, the concept of respect for autonomy making is gaining importance including in the world of healthcare particularly demonstrated in the emphasis on the importance of the practice of informed consent. This movement towards respecting patient’s autonomy in healthcare can also be seen in the Malaysian healthcare practice. The concept of consent in the Malaysian setting however, may be different from the conventional individual autonomy usually discussed in the Western settings. In Malaysia, it is not uncommon to include other persons in the decision-making process and often than not, their decisions and views may prove to be of more importance in the decision. As demonstrated, in the case of Gurmit Kaur vs Tung Shin Hospital in 2012 and the case of Abdul Razak Datuk Abu Samah v Raja Badrul Hisham in 2013 there may be a movement away from the individualistic model of autonomy in healthcare decision-making in the country. This outlook is however not new as many researches and papers had advocated for the importance of relational autonomy, familial autonomy and cultural autonomy in healthcare decision making. This study examine the concept of autonomy in healthcare decision making according to the family dynamics in Malaysians' major cultures and faiths. This is important in order to ensure the model of autonomy that is applied in Malaysia is sociocultural relevant and consistent with local values. Consequently, an ethical and legal implication of adopting of several models of autonomy is analyzed. Models of autonomy which are included in the research are individualistic autonomy, familial autonomy, relational autonomy as well as cultural autonomy in healthcare decision making will be conducted. To answer the two-tier research question, this research utilizes the library-research method. This study concluded that the Malaysian healthcare sector may want to acknowledge the relevance of other models of autonomy such as familial, relational and cultural autonomy in healthcare decision making according to patient’s preferences and needs. This study also proposes some recommendation in the decision-making process to enhance patient’s autonomy. Finally, this study concludes that there are still gaps in the current body of knowledge autonomy in general, and further studies are required for effective implementation of autonomy in decision-making in Malaysian healthcare settings.